Mutations of the Drosophila Myosin Regulatory Light Chain Affect Courtship Song and Reduce Reproductive Success - Chakravorty, Samya (Public Library of Science, 2014)
The Drosophila indirect flight muscles (IFM) rely on an enhanced stretch-activation response to generate high power output for flight. The IFM is neurally activated during the male courtship song, but its role, if any, in generating the small amplitude wing vibrations that produce the song is not known. Here, we examined the courtship song properties and mating behavior of three mutant strains of the myosin regulatory light chain (DMLC2) that are known to affect IFM contractile properties and impair flight: (i) Dmlc2(Δ2–46) (Ext), an N-terminal extension truncation; (ii) Dmlc2(S66A,S67A) (Phos), a disruption of two MLC kinase phosphorylation sites; and (iii) Dmlc2(Δ2–46;S66A,S67A) (Dual), expressing both mutations. Our results show that the Dmlc2 gene is pleiotropic and that mutations that have a profound effect on flight mechanics (Phos and Dual) have minimal effects on courtship song. None of the mutations affect interpulse interval (IPI), a determinant of species-specific song, and intrapulse frequency (IPF) compared to Control (Dmlc2(+) rescued null strain). However, abnormalities in the sine song (increased frequency) and the pulse song (increased cycles per pulse and pulse length) evident in Ext males are not apparent in Dual males suggesting that Ext and Phos interact differently in song and flight mechanics, given their known additive effect on the latter. All three mutant males produce a less vigorous pulse song and exhibit impaired mating behavior compared to Control males. As a result, females are less receptive to Ext, Phos, and Dual males when a Control male is present. These results open the possibility that DMLC2, and perhaps contractile protein genes in general, are partly under sexual selection. That mutations in DMLC2 manifest differently in song and flight suggest that this protein fulfills different roles in song and flight and that stretch activation plays a smaller role in song production than in flight.